Cytotoxic Steroidal Glycosides from the Whole Plant of Calamus acanthophyllus - Prawat, Hunsa; Mahidol, Chulabhorn; Kaweetripob, Wirongrong; Intachote, Pakamas; Pisutjaroenpong, Somchai; Ruchirawat, Somsak (Planta Medica, 2016)
A new steroidal glycoside, callaphylloside (1), together with seven known glycosides (2–8), was isolated from the whole plant of Calamus acanthophyllus. The structure of the new compound was elucidated by spectral data analyses and chemical transformations. Compounds 5 and 8 exhibited strong cytotoxic activity against four cancer cell lines (0.7 ≤ IC50 ≤ 3.4 µM). Evaluation of the structure-activity relationship among steroidal glycosides revealed that the structure of spirostanol with an α-L-rhamnopyranosyl linked to C-2 of the inner glucopyranosyl residue both play a critical role in the effects of these compounds on the cancer cell lines.
Keywords: Calamus acanthophyllus; Arecaceae; steroidal glycoside; cytotoxic activity